Avaliação tomográfica da espessura maxilar após enxerto ósseo em bloco autógeno e da sobrevida dos implantes na região. Proservação de cinco anos - Dutra, Rodrigo Aliprandi (2014)
The aim of retrospective investigation was to evaluate by means of computerized tomographic scans the increase in width using autogenous block graft from retromolar area and implant clinical success after 5-year follow-up. Eleven patients were underwent ridge augmentation using autogenous block graft. The computed tomography scans taken before, 6 months after surgery and 5 years after the ridge augmentation using autogenous block graft. After 6 months the implants were placed and measured torque values. The data were analyzed with paired t-test and non-parametric test (p=0.05). The average width of the lower portion of ridge initially and after 6 months and five years of reconstruction was respectively 3.67 mm, 6.88 mm and 6.11 mm with a gain average horizontal thickness of 3.21 mm graft after 6 months and 2.44 after 5 years. The average width of the upper ridge initially and after 6 months and five years of reconstruction was respectively 5.57 mm, 8.06 mm and 6.89 mm with a gain average horizontal thickness of 2.49 mm graft after 6 months and 1.32 after 5 years. The average increase in initial total thickness of the ridge after 6 months and five years of reconstruction was respectively 4.62 mm, 7.47 mm and 6.50 mm with a gain average horizontal thickness of 2.85 mm graft after 6 months and 1.88 mm after 5 years. The results showed a statistically significant difference in the mean increase in the initial width of the lower portion compared to 6 months and 5 years and on average increased more upper comparing the initial period and 6 months after reconstruction. Seventeen sites were augmented, the mean initial crest width measured 3.06 mm. The results showed a statically significant difference in width after 6 months (p<0.001). One patient developed paresthesia and one implant was lost. The 5-year survival of fixture was 94.12%. The width obtained with the surgery was effective for the installation of the implants in the maxillary. The presented technique of ridge augmentation using autogenous block grafts demonstrated successful horizontal ridge augmentation with high predictability.